ANTARA DEDIKASI DAN APRESIASI : POTRET DISPARITAS INSENTIF PENDIDIK NON FORMAL BIDANG KEAGAMAAN - Hidayah, Dita Nisaul; Taufiq, Amal (Jurnal PUBLIQUE, 2025)
This study aims to determine the implementation of incentives for non-formal religious educators in Bojonegoro Regency, a government policy program for community welfare. This study used a qualitative approach, with data collection techniques including observation, interviews, and documentation. The results indicate that two villages within the same sub-district both have non-formal religious educational institutions. However, one village receives incentives for non-formal religious educators while the other does not, resulting in a disparity in enrollment. However, this difference in enrollment does not diminish the motivation of the religious teachers at both educational institutions, who both teach sincerely to improve the religious knowledge of their students, who are the future of the nation. Robert K. Merton's structural functional theory is used as an analytical tool, explaining two functions: the first is the manifest function, such as the provision of incentives to appreciate educator dedication, improve welfare, and motivate professionalism. The second is the latent function, which is an invisible function, such as increasing community involvement, creating social inequality, and fostering dependence on government assistance.